PLK1 Interacts and Phosphorylates Axin That Is Essential for Proper Centrosome Formation - Ruan, Ka; Ye, Fan; Li, Chenyu; Liou, Yih-Cherng; Lin, Sheng-Cai; Lin, Shu-Yong (PLOS ONE, 2012)
Abnormal amplification of centrosomes could lead to improper chromosome segregation and aneuploidy and is implicated in cancer development. Here, we demonstrate that Axin, a scaffolding protein in Wnt signaling, is phosphorylated by PLK1 during mitosis. Phosphorylation of Axin Ser-157 by PLK1 abolished Axin association with γ-tubulin, while substitution of Ser-157 with alanine exhibited sustained interaction with γ-tubulin. In addition, overexpression of Axin-S157A significantly increased the number of cells with multi-centrosomes. These results suggest that the phosphorylation status of Axin, mediated by PLK1, dynamically regulates its association with γ-tubulin and centrosome formation and segregation.